Perspectives of public spaces in Irkutsk. Visions, Alliances, Requirements - Barbara Engel (Proekt Bajkal, 2013)
Open spaces are ‘backbones’ of the city, important places of communication and identification of the urban society. In an era of increasing privatization and commercialization of urban spaces the design of public spaces remains as one of the most important responsibilities for the municipality. The article discusses possibilities for improving public spaces in Irkutsk. Three conceptional approaches – 1: Network of public spaces, 2: Integration of different interests, 3: Encouraging special features and spatial identity – by presenting international best practices (e.g. from Dresden, Cleveland, Oulu) are recommended as approach for sustainable city development.